Diagnóstico sectorial de la actividad de asesoramiento técnico de arquitectura del cantón Loja - Morocho Marizaca, Juan Sebastián (2024)
The sectoral diagnosis helps to understand and evaluate the current state of a specific sector of the economy, providing insight into its challenges and prospects. It offers a solid tool for companies to make informed decisions using indicators or KPIs to measure performance. The purpose of the research is to conduct a sectorial diagnosis of architectural technical advice in the canton of Loja. This involves a mixed approach methodology with a cross-sectional design and exploratory-descriptive scope, using field observation and literature review to establish key success factors such as internal management, external coordination, customer management, etc. It also evaluates the financial and non-financial KPIs of the industry. The study found that the performance of this industry is acceptable in terms of financial KPIs. The liquidity is low at $0.86, the level of indebtedness of the microenterprises analyzed is 16%, and the average payment and collection periods are long at 209 and 157 days respectively. The net working capital of $3,904.53 provides sufficient solidity and an acceptable, but moderate level of ROA and ROE profitability. In relation to non-financial KPIs, the industry indicates efficient project management, an outsourcing percentage of 38%, a study hour cost close to the national average of $7.05, a level of training of office staff with certain shortcomings, low efficiency of advertising with 10.35%, and sufficient capacity to invest in technology. Overall, it's a sector with opportunities for improvement in its management, sensitive to external factors such as inflation or the political climate, profitable and a generator of economic growth in the country.